2018
DOI: 10.1111/ene.13577
|View full text |Cite
|
Sign up to set email alerts
|

Thrombectomy outcomes for acute stroke patients with anterior circulation tandem lesions: a clinical registry and an update of a systematic review with meta‐analysis

Abstract: Our data report an association between acute stenting and successful reperfusion rates in stroke patients with tandem lesion treated with MT. Further studies are warranted to determine the intracranial bleeding risk after MT and stenting according to the antiplatelet therapy.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
40
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
4
2
2

Relationship

0
8

Authors

Journals

citations
Cited by 63 publications
(52 citation statements)
references
References 27 publications
6
40
0
1
Order By: Relevance
“…A higher admission NIHSS score, a longer time to recanalization, and the absence of arterial reperfusion were found to be independent risk factors for death, with a mortality rate in our series of 20.2%. These results are in agreement with those previously reported, which describe sICH rates of 5-15% and mortality rates of 13.2-22% [8,12,[16][17][18]22], and they also similar to those published in 2 recent meta-analysis that reported an sICH rate of 7% and a mortality rate of 13-14% [9,10]. Likewise, a recent study found no differences in terms of hemorrhagic complications between patients presenting with an isolated intracranial occlusion compared to tandem occlusions, even after administration of antiplatelet therapy [23].…”
Section: Discussion/conclusionsupporting
confidence: 94%
See 1 more Smart Citation
“…A higher admission NIHSS score, a longer time to recanalization, and the absence of arterial reperfusion were found to be independent risk factors for death, with a mortality rate in our series of 20.2%. These results are in agreement with those previously reported, which describe sICH rates of 5-15% and mortality rates of 13.2-22% [8,12,[16][17][18]22], and they also similar to those published in 2 recent meta-analysis that reported an sICH rate of 7% and a mortality rate of 13-14% [9,10]. Likewise, a recent study found no differences in terms of hemorrhagic complications between patients presenting with an isolated intracranial occlusion compared to tandem occlusions, even after administration of antiplatelet therapy [23].…”
Section: Discussion/conclusionsupporting
confidence: 94%
“…These results are also in line with those reported in acute ischemic stroke with isolated intracranial occlusions [8]. Similar data were reported in 2 recent meta-analyses, with rates of 53% for good clinical outcome at 3 months (95% CI 43-62) in the study of Sadeh-Gonik et al [9] and 44% (95% CI 33-55) in the study of Sivan-Hoffmann et al [10]. Lastly, a subanalysis of the ESCAPE study in patients with tandem occlusions showed a favorable outcome at 3 months in 60% of the cases [11].…”
Section: Discussion/conclusionsupporting
confidence: 91%
“…The data are synthetized in 2 recently published meta-analyses. 7,11 Most articles reported high recanalization rates with different technical variations of the procedure and identified predictors of successful recanalization and/or good clinical outcome. Surprisingly, there was very little information on the outcome of implanted carotid stents.…”
Section: Discussionmentioning
confidence: 99%
“…In most instances, these examples were explicit about their rationale for incorporating unpublished data, primarily because the published data was sparse or lacked granularity (i.e., to increase certainty of findings by addressing strength of evidence), and/or to determine whether the published data were applicable to health system populations (i.e., to increase the certainty of findings by addressing the applicability of evidence). [5][6][7][8][9][10][11][12][13][14][15][16][17][18] For example, we identified several times that the Mayo Clinic combined local health system data with systematically reviewed published data to support various clinical groups' patient care management decisions, that illustrate different reasons for combining unpublished local data and published data:…”
Section: Inform Strength Application or Implementation Of Evidencementioning
confidence: 99%
“…Based on selected examples, demonstrating concordance can increase the certainty for decision makers and result in practice change or coverage decisions. 12,17,18,22 • Last, we believe this process should be conducted in close partnership with health systems, which ideally includes a range of individuals such as clinical leaders and decision makers as well as QI staff and health system researchers.…”
Section: Recommendationsmentioning
confidence: 99%